Hematogenous dissemination of pulmonary mucormycosis manifested as multiple subcutaneous nodules: a case report and review of the literature - Apiradee Taweesuk (2022)
Background: Disseminated mucormycosis presenting with multiple subcutaneous nodules is a rare condition with a poor prognosis, and delayed diagnosis and treatment is common. Case presentation: We report a case of 64-year-old Thai woman with colorectal cancer who initially presented with Acinetobacter baumannii pneumonia and respiratory failure. Following 10 days after her admission to the intensive care unit, she developed hospital-acquired pneumonia. Five days later, multiple subcutaneous nodules appeared on both arms and both legs. Bronchoalveolar lavage and skin biopsy cultures both grew Mucor spp. She was diagnosed with disseminated mucormycosis and was treated with liposomal amphotericin B at a dose of 5 mg/kg/day. Despite treatment, our patient succumbed to septic shock and multiorgan failure on the third day after definitive diagnosis. Conclusions: This case demonstrates that the subcutaneous nodules caused by hematogenously disseminated mucormycosis are unusual in a patient with a solid tumor. Clinicians should be aware of this atypical presentation of mucormycosis in patients with solid tumors.